Studying the Effect of the Anabolic Androgen Methandrostenolone on Some Fertility Parameters in Local Male Rabbits - Mohamed Mohsen Khalaf, Jamil K. Wali (Pakistan Journal of Medical & Health Sciences, 2022)
The current study was conducted to investigate the effect of the anabolic androgen Methandrostenolone (Dianabol) on some parameters of fertility in male rabbits. In this experiment, (20) adult male rabbits were used, randomly divided into two groups, each group 10 animals. Control group: The animals were dosed with distilled water. The treatment group: The animals were orally dosed with (Dianabol) within a course that lasted (8) weeks in an ascending manner: (0.076, 0.152, 0.304, 0.38, 0.456, 0.532, 0.608, 0.684) mg/kg/d each dose for consecutive 7days. In the end of the experiment period the results showed a significant decrease (P≤ 0.05) in the ratio of testes and epididymis weight to the body weight of the animal in addition to tissue damage that included a significant decrease (P≤0.05) in the level of germinal epithelium height of the seminiferous tubules and a significant decrease (P≤0.05) in the thickness of the epididymis wall, also our results showed a significant decrease (P<0.05) in the total number of sperm, sperm motility and survival rate in the treatment group animals compared with control group animals. We conclude from this study that anabolic androgen Methandrostenolone has a significant negative effect on fertility in male rabbits.